Involvement of the Ventrolateral Periaqueductal Gray Matter-Central Medial Thalamic Nucleus-Basolateral Amygdala Pathway in Neuropathic Pain Regulation of Rats - Sun, Yi; Wang, Jian; Liang, Shao-Hua; Ge, Jun; Lu, Ya-Cheng; Li, Jia-Ni; Chen, Yan-Bing; Luo, Dao-Shu; Li, Hui; Li, Yun-Qing (Frontiers in Neuroanatomy, 2020)
The central medial nucleus (CM), a prominent cell group of the intralaminar nuclei of the thalamus and the ventrolateral periaqueductal gray matter (vlPAG), are two major components of the medial pain system. Whether the vlPAG and CM are input sources of nociceptive information to the basolateral amygdala (BLA) and whether they are involved in neuropathic pain regulation remains unclear. Clarifying the hierarchical organization of these subcortical nuclei (vlPAG, CM and BLA) can enhance our understanding on the neural circuits for pain regulation. Behavioral tests showed that CM lesion made by kainic acid (KA) injection could effectively alleviate mechanical hyperalgesia in 4, 6, and 8 d after spared nerve injury (SNI) surgery, with the symptoms returning back after 10 d. Morphological studies revealed that: (1) the CM received afferents from the vlPAG and sent efferents to the BLA, indicating that there exists an indirect vlPAG-CM-BLA pathway; (2) such CM-BLA projections were primarily excitatory glutaminergic neurons as revealed by fluorescence in situ hybridization; (3) the fibers originated from the CM formed close contacts with both excitatory and inhibitory neurons in the BLA; (4) BLA projecting CM neurons expressed Fos induced by SNI and formed close contacts with fibers form vlPAG, suggesting the vlPAG-CM-BLA indirect pathway was activated in neuropathic pain conditions. Finally, the vlPAG-CM-BLA indirect pathway was further confirmed by using anterograde and monosynaptic virus tracing investigation. In summary, our present results provide behavioral and morphological evidences for that the indirect vlPAG-CM-BLA pathway might be a novel pain pathway involved in neuropathic pain regulation.